Homologous recombination and evolutionary arms race drive the adaptive evolution of African swine fever virus - Wenqiang Wang; Qinqiu Liu; Qilin Zhao; Zhenbang Zhu; Wei Wen; Zhendong Zhang; Xiangdong Li (Veterinary Research)
Abstract African Swine Fever Virus (ASFV) is a highly contagious pathogen responsible for substantial economic losses in swine populations worldwide. Despite extensive research, the mechanisms underlying the genomic evolution of ASFV remain poorly understood. In this study, we conducted a comprehensive analysis of ASFV evolutionary strategies by examining 252 complete ASFV genomes. Our pan-genome analysis categorizes ASFV genes into core and non-core categories, with core genes predominantly locate in the central region of the genome, while non-core genes are primarily situated at the variable genomic termini, exhibiting higher rates of genetic loss and diversification. Gene synteny analysis revealed that ASFV inherited a portion of its core gene repertoire from the common ancestor of the Asfarviridae family, establishing its central genomic framework, and acquired virus-specific genes that contributed to its distinct genetic identity during divergence. Homologous recombination analysis identified 76 genes exhibiting strong recombination signals, emphasizing the critical role of recombination in ASFV evolution. Additionally, 9 genes were found to be under positive selection, highlighting the influence of the host-virus evolutionary arms race in shaping ASFV genome, particularly in terms of immune evasion and host interaction. These findings underscore the dynamic evolutionary forces driving ASFV adaptive evolution and provide important implications for understanding the virus global spread and the development of effective control measures.